Treatment-Related Mortality in Children with Acute Lymphoblastic Leukaemia at a Tertiary Care Hospital of Multan - Muhammad Shahzad Maqsood, Zulfiqar Ali Rana, Muhammad Kamran Adil, Muhammad Zahid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The present study aimed to assess the frequency of treatment related mortality (TRM) among all ALL related mortalities recorded in the paediatric ward. Methods: A cross-sectional study was undertaken at the Department of Pediatric, Children’s Hospital and the Institute of Child Health, Multan, Pakistan between January 2021 and June 2022. The study enrolled all children under the age of 18 years who were diagnosed with acute lymphoblastic leukaemia. Data of individuals who died secondary to a relapsing or progressive disease or those who had not yet started chemotherapy were excluded. The main focus of the study was to measure TRM. All data were collected in pre-defined pro forma. Results: A total of 205 deaths among ALL patients were reported during the study. Of these, 120 (58.54%) cases were associated with TRM. The most common type of ALL immunophenotype was B-cell ALL in 100 patients. Majority of the patients who suffered from TRM were at the induction phase i.e. 69 (57.50%). The most common cause of TRM was sepsis i.e. 100 (83.33%) cases. The second most common cause of TRM was haemorrhagic complications. Conclusion: The results indicated that TRM was a significant contributor to treatment failure in this population. Out of a total of 205 deaths, more than half were attributed to TRM. Among the 100 patients evaluated, B-cell ALL was the most prevalent type. The majority of TRM cases occurred during the induction phase (57.50%), and sepsis was identified as the primary cause of TRM, followed by haemorrhagic complications. Keywords: Acute lymphoblastic leukaemia, ALL, chemotherapy, febrile neutropenia, paediatric cancer, sepsis, treatment-related mortality, TRM